2015
DOI: 10.1097/sla.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Gastrointestinal Stromal Tumor

Abstract: E-GIST enucleation seems safe for tumors of less than 65 mm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Enucleation surgery can be an alternative method which has a lower morbidity rate. Robb et al (14) showed that enucleation was safe for esophageal GIST cases, especially when smaller than 65 mm, considering an intact pseudocapsule with negative microscopic margins preserved. This patient was free of disease for 49 months by enucleation with clear margins.…”
Section: Discussionmentioning
confidence: 99%
“…Enucleation surgery can be an alternative method which has a lower morbidity rate. Robb et al (14) showed that enucleation was safe for esophageal GIST cases, especially when smaller than 65 mm, considering an intact pseudocapsule with negative microscopic margins preserved. This patient was free of disease for 49 months by enucleation with clear margins.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these tumors are associated with nonspecific symptoms (early satiety, swelling) unless they ulcerate, bleed or grow enough to cause pain, obstruct, or present other manifestations related to their disproportionate size[ 12 , 13 ]. In the case of esophageal GIST, dysphagia represents the first specific symptom in this location[ 14 ].…”
Section: Role Of Clinicianmentioning
confidence: 99%
“…Robb et al[ 14 ] proposed that enucleation of the tumor is safe for esophageal GISTs < 65 mm as long as negative margins and intact pseudocapsule can be achieved, while in tumors of > 90 mm with evidence of mucosal ulceration and/or a high mitotic activity, an esophagectomy should be performed. The choice between esophagectomy and enucleation for tumors of between 65 and 90 mm needs further clarification with the decision being influenced by the location, malignant risk, patient comorbidity, and the presence of mucosal affectation[ 14 , 70 ]. Neoadjuvant therapy is indicated with the aim of shrinking the primary tumor[ 70 ].…”
Section: Resactable Diseasementioning
confidence: 99%
See 1 more Smart Citation